DEVELOPING A CONTEXTUAL BOOK FOR PRONUNCIATION AND SPEAKING PRACTICE - Haryani, Tiara Retno (English Department of Faculty of Tarbiyah and Teacher Training, 2018)
Pronunciation is considered very essential for language learners since it can influence their communication process. Nevertheless, learning pronunciation becomes a complex aspect to master a language, especially English. Therefore, there are many errors and mistakes committed by English learner in pronunciation. In a previous research, the error of pronunciation had been investigated. There were some factors affecting the error. Based on the pronunciation test, there are some errors produced by the students in performing their speaking skill and pronunciation practice. Some aspects affecting the errors are also discovered from the interview. There are also several effects caused by the pronunciation error faced by the students. In short, there are certain errors in pronunciation produced by the English department student as the result of various aspects in their learning process. Therefore, there is a need to develop a set of materials for their practice in pronunciation to solve the students? problem.